IMPLEMENTASI PEMBELAJARAN PAI BERBASIS ADAT BASANDI SYARAK, SYARAK BASANDI KITABULLAH DI SMKN 1 PALEMBAYAN, KEC. PALEMBAYAN, KAB. AGAM - Fitria Sesmeri; Alimir Alimir; Darul Ilmi; Jasmienti Jasmienti (KOLONI, 2022)
In the implementation of Islamic religious education learning based on the adat-based syarak, there are still some shortcomings in carrying out Islamic religious education learning, judging from the opening, core, and closing activities in classroom learning, there is still a learning process in the classroom that does not run properly. Some of the teachers also have not implemented the adat basandi syarak, syarak basandi Kitabullah in Islamic religious education subjects for class X concerning self-control (mujahadah annafs), good prejudice (husnuzzan), and brotherhood (ukhuwah) and promiscuity and adultery are prohibited by religion. , the teacher's core activities only explain learning, in the core activities of learning Islamic religious education teachers carry out learning in general. This type of research uses descriptive qualitative research methods. The location of this research is in SMK Negeri 1 Palembayan, Kec. Palembang, Kab. Religion and researchers took this location because here the researchers found problems that needed to be discussed and important to be studied. With key informants, namely teachers of Islamic religious education and supporting informants, namely students and principals of SMK N 1 Palembayan. To collect data, the authors conducted observations, interviews, and documentation. After the data is collected, data processing and analysis is carried out. Furthermore, testing the validity of the data by means of triangulation of data. Based on the results of the research conducted, in learning Islamic religious education based on the Basandi Syrak custom, the Kitabullah Basandi Syarak has been going well, before doing other activities the teacher opens the lesson by reading greetings and giving a proverb to provide motivation to learn to students, then the teacher conducts opening activities. other. Keywords: PAI Learning, Indigenous Basandi Syarak, Syarak Basandi Kitabullah